Estudio del mecanismo de reacción de tostación de la calcopirita en distintas atmósferas. - Casa Correa, Edwin Ricardo (2025)
This study investigates the reaction mechanism of chalcopyrite under roasting conditions in both oxidizing and inert atmospheres, using two mineral concentrate fractions: a coarse fraction (74–100 µm) and a fine fraction (38–53 µm), each exhibiting distinct mineralogical and chemical compositions. Through controlled roasting and leaching experiments, complemented by X-ray Diffraction (XRD), X-ray Fluorescence (XRF), Nitrogen physisorption analysis, and Scanning Electron Microscopy (SEM), the influence of temperature, atmosphere, and particle size on the transformation of copper species was evaluated. The results demonstrate that a temperature of 600°C and an oxidizing atmosphere maximize the conversion of chalcopyrite to copper sulfates and oxides, allowing for recoveries of nearly 80% Cu. Kinetic analysis revealed a shift in the controlling mechanism, from a regime dominated by surface chemical reactions in the early stages of roasting to one dominated by O2 diffusion through the ash layer over extended periods. It was identified that the fine fraction, richer in chalcopyrite and copper, favors the formation of soluble species, while the coarse fraction, with higher levels of pyrite, limits metal conversion and recovery. In conclusion, the selectivity of products formed during roasting is determined not only by operating conditions but also by the initial concentrate composition, temperature, and atmosphere. These findings contribute to the optimization of metallurgical roasting processes, enabling more efficient utilization of mineral resources.